RESULTS CONCERNING THE ESTABLISHMENT OF THE BEST POLLINATORS TO SOME OF THE NEW CHERRY CULTIVARS - Elena Iurea; Gica Gradinariu; Sorina Sarbu; Gelu Corneanu (Fruit Growing Research, 2013)
The aim of this paper work is the rating of the polen’s quality, the study of the fertilty indexes and the behaviour of the cultivars in the proces of controled polination for some of the cultivars obtained at RSFG Iasi, for establishing the compatible groups on this criteria. The researches were made in 201 and 2012 at RSFG Iasi, with 9 chery cultivars as study material (‘Ludovic’, ‘Cociu’, ‘Margo’, ‘Alex’, ‘Anda’, ‘Iosif’, ‘Andrei’, ‘Mihai’ and ‘Paul’). Folowing the data analysis concerning the cultivars behaviour in the polination proces, there are recommended the interfertile groups presented in table 3. To obtain good productions each year, it is necesary to provide optimal conditions for interpolination for the cultivars by their corect alocation in orchard, planting a row with polinator chery at 2 or 4 rows of chery tres for polination (the report of 2:1 or 4:1).